A functional network of highly pure enteric neurons in a dish - Caillaud, Martial; Le Dréan, Morgane E.; De-Guilhem-de-Lataillade, Adrien; Le Berre-Scoul, Catherine; Montnach, Jérôme; Nedellec, Steven; Loussouarn, Gildas; Paillé, Vincent; Neunlist, Michel; Boudin, Hélène (Frontiers in Neuroscience, 2023)
The enteric nervous system (ENS) is the intrinsic nervous system that innervates the entire digestive tract and regulates major digestive functions. Recent evidence has shown that functions of the ENS critically rely on enteric neuronal connectivity; however, experimental models to decipher the underlying mechanisms are limited. Compared to the central nervous system, for which pure neuronal cultures have been developed for decades and are recognized as a reference in the field of neuroscience, an equivalent model for enteric neurons is lacking. In this study, we developed a novel model of highly pure rat embryonic enteric neurons with dense and functional synaptic networks. The methodology is simple and relatively fast. We characterized enteric neurons using immunohistochemical, morphological, and electrophysiological approaches. In particular, we demonstrated the applicability of this culture model to multi-electrode array technology as a new approach for monitoring enteric neuronal network activity. This in vitro model of highly pure enteric neurons represents a valuable new tool for better understanding the mechanisms involved in the establishment and maintenance of enteric neuron synaptic connectivity and functional networks.